(untitled) (Gestão & Regionalidade, 2025)
Sustainable food choices represent a commitment to the future of the planet. This study addresses global challenges in the food system, emphasizing the need for sustainable approaches recognized by the United Nations. The analysis of the interaction between purchase intention, sustainability perception, product attributes, sustainable attitude, and gender was conducted through a quantitative analysis inspired by the study of Van Loo et al. (2017). The sample, consisting of 206 participants, revealed significant interactions between purchase intention, product attributes, and sustainable attitude, with women showing a greater inclination toward sustainability. This study contributes to the theory by expanding the original research in a diverse context. In practical terms, it guides businesses on marketing strategies, emphasizing the importance of considering product attributes and sustainable attitudes to promote conscious consumption, as well as influencing public policies on regulation and information.